Pengaruh Green Accounting dan Material Flow Cost Accounting Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening - Agatha, Sherina Natasya; Widoretno, Astrini Aning (Universitas Muhammadiyah Metro, 2023)
This research aims to examine and illustrate the effect way of green accounting andmaterial flow cost accounting (MFCA) on company value through profitability incompanies in the basic and chemical industry sector in 2018-2021. The populationin this study is companies in the basic and chemical industry in BEI totalling 13companies according to sample criteria, with a research period 4 years then samplein this study is 52 sample. This study used a quantitative methodology, usingsecondary data in the form of annual reports of basic and chemical industrycompanies. Data utilized in this research using purposive sampling techniques anddata analysis using Smart PLS. The results of this study indicate that neither greenaccounting and MFCA have no affect on company value, while either greenaccounting and MFCA have an effect on profitability. Green accounting and MFCAhave no affect on company value through profitability